If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Simplifying x^{2}+ 5x + -59 = 0 Reorder the terms: -59 + 5x + x^{2}= 0 Solving -59 + 5x + x^{2}= 0 Solving for variable 'x'. Begin completing the square. Move the constant term to the right: Add '59' to each side of the equation. -59 + 5x + 59 + x^{2}= 0 + 59 Reorder the terms: -59 + 59 + 5x + x^{2}= 0 + 59 Combine like terms: -59 + 59 = 0 0 + 5x + x^{2}= 0 + 59 5x + x^{2}= 0 + 59 Combine like terms: 0 + 59 = 59 5x + x^{2}= 59 The x term is 5x. Take half its coefficient (2.5). Square it (6.25) and add it to both sides. Add '6.25' to each side of the equation. 5x + 6.25 + x^{2}= 59 + 6.25 Reorder the terms: 6.25 + 5x + x^{2}= 59 + 6.25 Combine like terms: 59 + 6.25 = 65.25 6.25 + 5x + x^{2}= 65.25 Factor a perfect square on the left side: (x + 2.5)(x + 2.5) = 65.25 Calculate the square root of the right side: 8.077747211 Break this problem into two subproblems by setting (x + 2.5) equal to 8.077747211 and -8.077747211.## Subproblem 1

x + 2.5 = 8.077747211 Simplifying x + 2.5 = 8.077747211 Reorder the terms: 2.5 + x = 8.077747211 Solving 2.5 + x = 8.077747211 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2.5' to each side of the equation. 2.5 + -2.5 + x = 8.077747211 + -2.5 Combine like terms: 2.5 + -2.5 = 0.0 0.0 + x = 8.077747211 + -2.5 x = 8.077747211 + -2.5 Combine like terms: 8.077747211 + -2.5 = 5.577747211 x = 5.577747211 Simplifying x = 5.577747211## Subproblem 2

x + 2.5 = -8.077747211 Simplifying x + 2.5 = -8.077747211 Reorder the terms: 2.5 + x = -8.077747211 Solving 2.5 + x = -8.077747211 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2.5' to each side of the equation. 2.5 + -2.5 + x = -8.077747211 + -2.5 Combine like terms: 2.5 + -2.5 = 0.0 0.0 + x = -8.077747211 + -2.5 x = -8.077747211 + -2.5 Combine like terms: -8.077747211 + -2.5 = -10.577747211 x = -10.577747211 Simplifying x = -10.577747211## Solution

The solution to the problem is based on the solutions from the subproblems. x = {5.577747211, -10.577747211}

| 2x+10-6x=13-13x+9x-3 | | 3n+3z= | | 2x^3-6x^2-6x+18=0 | | m-4=26 | | p=3n+3z | | m+6=74 | | 5+6(w+2)+w= | | 3z+3n= | | 3x^2+36-6=0 | | 121=8x+4x+2x+x+x | | 5n=100 | | 7x^2-13x-6=0 | | 121=8x+4x+4x+2x+x+x | | -8+r=28 | | x+4=7x+10 | | 28=18-2z | | 5(2x+1.2)=4(x+5) | | 18c+3-16c=11 | | y=5-x-x^2 | | -4(24+8y)=64 | | 7a-10=20-3a | | 8x-9=9x+2 | | 8(12+4x)=64 | | a+4b=21 | | 10x-8=8x | | 6(y+8)+y=2(y+4)-5 | | 2+4x-3+7x= | | 6+3x=63 | | y=3x^2+1 | | 9+4x-3+7x= | | x-9x+7x-4x= | | 27+(-9)= | | 4n^2-17=19 | | 8x+y=-27 | | 9-5x+2=4-5x | | 4(x+1)=2x+7 | | [0.15(607.66-442)+35.40]= | | x^2-1.2x+0.36=0 | | 3r^2-16r-2=0 | | [0.15(532.70-204)+16.40]= | | 2x+x^2= | | (x+5)(x-6)=-26 | | y-4(1)=0 | | 1=-.25x+5+.75x | | 14x-21y+63=0 | | 7x+(-2x)+x=52 | | x^4-11x^2-18=0 | | 4x(2)+4x+4y(2)+32y-191=0 | | [0.28(1888.85-1648)+327.40]= | | 5x^2+5x-50=0 | | 2.5x+1.8y=60 | | 7x+5-3x=20x+15 | | x^2-8x=10 | | [(1+x^2)(2x)-(x^2)(2x)]= | | [0.10(921.14-304)+0]= | | 5-(x+5)=30 | | 8x^2-8w+2=0 | | (6x-4)(5x+3)=0 | | [0.15(1863.32-1038)+70.90]= | | 3x^2-8x-9=0 | | (x+6)(x-7)(4x-5)=0 | | s+5s-155=565 | | 6-8(x+3)+5x=5x-(2x-5)+13 | | 3T+7S=380 | | 3x-4y=-15 |